ANALISIS PROSES SELEKSI DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN BAGIAN REDAKSI PT. RIAU POS PEKANBARU - Dewi Rismala Siburian; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Selection is process of get applicant who precise by several specific step that havepurpose to get employee approriate with need of enterprise and hope future haveinfluence to good performance. The step of selection in this research are formapplication work, pshycotest, sample test work, and interview test.Performance is achievement level work through ability and effort that haveemployee where in performance valued are six aspect that is quality, knowledge aboutwork, teamwork, initiative, integrity, and quality personal.PT. Riau Pos Pekanbaru is enterprise of sector publication newspaper that olderand already sturdy as market leader where in this enterprise editorial staff departmenthave important role of contents newspaper because editorial staff department thatsearching news, selecting news, and editing news until needed human resources that havequality high that can get when process selection go on and when process mentionedeffective will be performance good performance.Based on result analysis of research show that selection have positive influence toperformance employee performance editorial staff department of PT. Riau PosPekanbaru. This can be viewed of analysis data that known of t arithmetic(5,559) > ttabel (2,080) and sig (0,000) < 0,05. So, the hipotesis of this research that explain thereis influence selection to performance can be accepted.Keywords : Selection, Performance, Influence